Screening and quantification of inorganic anions in Shilajit and its supplements - Elham Kamgar; Joanna Zembrzuska; Wiktor Lorenc; Massoud Kaykhaii (BMC Chemistry)
Abstract Shilajit, a natural substance with ancient medicinal roots, is increasingly used in modern supplements for its purported health benefits. However, there is a lack of comprehensive chemical characterization, particularly regarding inorganic anions. This study addresses this gap by quantifying common inorganic anions in 14 raw Shilajit samples sourced from Iran, India, Nepal, Kyrgyzstan, and Russia, as well as in 6 commercially available supplements from Poland, Russia, and Kyrgyzstan. Using ion chromatography, key anions including chloride, sulphate, nitrate, hydrogen phosphate, and fluoride were analyzed. Results revealed that chloride was the most prevalent anion, with concentrations ranging from 0.102 to 9.496 mg.g− 1 in raw Shilajit samples and up to 0.931 mg.g− 1 in supplements. Sulphate levels were significant, with concentrations up to 12.412 mg.g− 1 in raw Shilajit and 0.854 mg.g− 1 in supplements. Nitrate was detected in lower concentrations, peaking at 9.504 mg.g− 1 in raw Shilajit. Fluoride was quantifiable in only one sample at 0.064 mg.g− 1. The study concludes that Shilajit’s geographical origin significantly influences its anion composition, leading to variability in its potential health effects. These findings highlight the necessity for standardized formulations and stringent quality control measures in Shilajit supplement production to ensure consumer safety and product efficacy.